EFFECT OF THE MASS OF ZEOLITE IN CURCUMIN SOLUTION ON THE ADSORPTION PROCESS MEASURED WITH LUXMETER - Salwa Hapsotu Sa'adah (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2022)
ABSTRACT The purpose of this study was to show the effect of the mass of zeolite in curcumin solution on the adsorption process as measured by a luxmeter. Adsorption research using the batch system method is carried out with a number of Erlenmeyer glasses containing a solution containing certain substances to be adsorbed at a certain volume . Zeolite was used as an adsorbent with a size of 0.2 cm and a mass variation of 0.2; 0.4; 0.6; and 0.8 grams. Turmeric solution was specified as a model dye and this solution was linked to a commercially available zeolite. Then the measurement results are compared with several adsorption isotherm models, such as: Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, Jovanovic, Harkin-Jura, and Halsey models. As for the results showed that the zeolite can absorb dye, and the isotherm model has a linearity parameter of R² above 80% . The absorption and diffusion properties of zeolite are caused by the presence of different canal sizes and various cavities, because of which zeolite can also absorb dye from the turmeric solution. With this research, we gain experience and understanding of the concept of adsorption, it is hoped that it can also be applied in water and air purification.